Manajemen Program Pengembangan Kurikulum PAI dan Budi Pekerti dalam Pembentukan Karakter Religius Siswa: Management of IRE Curriculum Development Program and Character in Forming Student's Religious Character - Poetri Leharia Pakpahan; Umi Habibah (Tafkir: Interdisciplinary Journal of Islamic Education, 2021)
The research was a qualitative study using a case description in the elementary Muhammadiyah Macanan. The informans are head master of elementary Muhammadiyah Mcanan, PAI dan Budi Pekerti’s teacher, coordinator of curriculum, Thafidz’s teacher, teacher’s class, and fifth graders. The technique for collecting datas are used observations, and documentations, and indepth interviews. And the result showed that: 1) manajement of curriculum development program PAI dan Budi Pekerti used four functions management, they are a) Plannings arranged in the vision, missions, and objectives of the program, and the various programs, they are short term, medium-term, and long term programs  b) Organizing of human resources involved in the preparation of program and graduation competency standards, c) Implementations of development program are devided to dhuha prayers, dzuhur prayers, jum’at prayers, reading the holly Qur’an, and memorizing the qur’an. And content standards consisting of core competencies and basic competencies d) Evaluations are devided to achievement of planning, organizing, and implementing through graduation competency standards in dimency of attitude and skills. 2) The building of religious characters are devided to a) the teacher’s way how to provide the building religious characters; b) the teacher’s way to do the building religious characters; c) habituation methods in building religious characters.